Eksplorasi Etnomatematika pada Rumah Gudang Betawi - Aziza Fajriah; Firdha Annisa; Sopie Halimah; Vaniatul Lativa (International Forum of Researchers and Lecturers, 2023)
The branch of mathematics that studies history is usually known as ethnomathematics, and the concept of ethnomathematics has made a major contribution to improving mathematics learning. It turns out that many cultures cannot be separated from mathematical calculations, including historical buildings that are simple but have many meanings and meanings. So this research was conducted to describe and identify mathematical concepts in Betawi Warehouses in the Setu Babakan Betawi Cultural Village. The research method used is a descriptive qualitative method with an ethnographic approach. The results of the research show that there is a mathematical concept in the Gudang Betawi house building in the Setu Babakan Betawi Cultural Village, namely the shape of the Gudang Betawi house which has a rectangular pattern from front to back, there are many philosophies in ornaments that have sizes and shapes, and there are geometric elements found in the building. Betawi Warehouse Houses are like whole numbers in measuring activities, equivalent comparisons in calculating the length of time to build a Warehouse House, there are corners in the building, there are flat geometric elements found in the length, area and perimeter of the building, there is also space geometry which has content and volume , there is a geometric transformation in the ornamental part of the Gudang Betawi house, and there is a congruence of flat shapes that can be seen on the door of the Gudang Betawi house.